Influence of Diet on Bowel Function and Abdominal Symptoms in Children and Adolescents with Hirschsprung Disease-A Multinational Patient-Reported Outcome Survey - Judith Lindert; Hannah Day; Marta de Andres Crespo; Eva Amerstorfer; Sabine Alexander; Manouk Backes; Carlotta de Filippo; Andrzej Golebiewski; Paola Midrio; Mazeena Mohideen; Anna Modrzyk; Anette Lemli; et al. (MDPI AG, 2024)
Introduction: This study aimed to understand the influence of diet and nutrition items on gastrointestinal symptoms in patients with Hirschsprung Disease (HD). Method: An online questionnaire was created to obtain patient-reported outcomes using the multinational Holistic Care in Hirschsprung Disease Network. This was distributed in Dutch, English, German, Italian, Polish, and Swedish via patient associations. Information on demographics, the extension of disease, current diet, and the influence of food ingredients on bowel function were obtained. Results: In total, 563 questionnaires were answered by parents or patients themselves. The length of the aganglionic segment was short in 33%, long in 45%, total colonic aganglionosis (TCA) in 11%, and involved the small intestine in 10%. Overall, 90% reported following a mixed diet, and 31% reported taking probiotics, with twice as many patients taking probiotics in the TCA group compared to standard HD. Mealtimes and behaviours around eating were affected by 61%, while 77% had established food items that worsened symptoms, and of these, 80% stated that they had worked these items out themselves. A high-fibre diet was followed by 24% and 18% a low-fibre diet. Symptoms were reported, particularly from dairy in 30%, fruits in 39%, pulses in 54%, and sugar in 48%. Conclusions: This first multinational survey on diet and bowel function in HD reports an association between certain dietary items with gastrointestinal symptoms. This study can support an improved understanding of the interaction between food items and bowel function in children with HD. We suggest a multidisciplinary approach to balance dietary exclusions and support adequate growth, preventing nutrition deficiencies and enhancing quality of life.